Personal space in schizophrenic patients - Deuš, Valentina (Array, 2006)
Backgrund: Personal space is the area individuals maintain around themselves into which others cannot intrude without arousing discomfort. Objective: We tested the hypotheses that personal space of patients with schizophrenia would be a characteristic of 1) diagnosis 2) experimenter gender and/or 3) type of schizophrenic disorder. Subjects: For this aim, 114 schizophrenic and 120 age and gender matching adults with no history of mental illness participated in the study. Method: Personal space was assessed using stop-distance technique. All subjects were approached by female and male experimenter from four directions. Results: Personal space zone is significantly larger in schizophrenic patients than in comparison group. Subjects in both groups maintain larger personal space zone when approached by male experimenter. Between subjects diagnosed with paranoid and residual type of schizophrenia no significant difference in preffered interpersonal distances was found. Conclusions: The results suggest that schizophrenic patients, presumably due to their mental health, demonstrate stronger need for personal space. These results are consistent with protective function of personal space.